Multimodal evoked potentials are useful for the diagnosis of pediatric acute disseminated encephalomyelitis - Jing Liu; Mei Jin; Meijie Zhang; Yonggang Wang; Suzhen Sun (BMC, 2024)
Abstract Background The application of evoked potentials (EPs) to the diagnosis of acute disseminated encephalomyelitis (ADEM ) has not been investigated in detail. The aim of this study, therefore, was to analyze the value of multimodal EPs in the early diagnosis of pediatric ADEM. Methods This was a retrospective study in which we enrolled pediatric ADEM patients and controls (Cs) from neurology units between 2017 and 2021. We measured indices in patients using brainstem auditory evoked potentials (BAEPs), visual evoked potentials (VEPs) and somatosensory evoked potentials (SEPs), and then we analyzed their early diagnostic value in ADEM patients. Results The mean age of the ADEM group was 6.15 ± 3.28 years (range,1-12 years) and the male/female ratio was 2.1:1 The mean age of the Cs was 5.97 ± 3.40 years (range,1-12 years) and the male/female ratio was 1.3:1. As we used magnetic resonance imaging (MRI) as the diagnostic criterion, the sensitivity, specificity, and accuracy (κ was 0.88) of multimodal EPs were highly consistent with those of MRI; and the validity could be ranked in the following order with respect to the diagnosis of ADEM: multimodal Eps > single SEP > single VEP > single BAEP. Of 34 patients with ADEM, abnormalities in multimodal EPs were 94.12%, while abnormalities in single VEPs, BAEPs and SEPs were 70.59%,64.71%and 85.3%, respectively. We noted significant differences between single VEP/BAEPs and multimodal EPs (χ2 = 6.476/8.995,P = 0.011/0.003). Conclusions The combined application of multimodal EPs was superior to BAEPs, VEPs, or SEPs alone in detecting the existence of central nerve demyelination, and we hypothesize that these modalities will be applicable in the early diagnosis of ADEM.